Factors affecting Salmonella-based combination immunotherapy for prevention of type 1 diabetes in non-obese diabetic mice. Issue 52 (18th December 2018) - Husseiny, Mohamed I.; Du, Weiting; Mbongue, Jacques; Lenz, Ayelet; Rawson, Jeffrey; Kandeel, Fouad; Ferreri, Kevin
Highlights: Oral Salmonella -based vaccine induces tolerance in a murine model of T1D. Increasing vaccine autoantigen levels has no effect on the onset of diabetes. Salmonella -based vaccine combined with anti-CD3 enhances the effect against T1D. Reducing the doses of Salmonella -based vaccine therapy is sufficient to prevent T1D. Combination vaccine enhances regulatory mechanisms and suppresses autoimmunity. Abstract: We previously reported the development of an oral vaccine for diabetes based on live attenuated S almonella -expressing preproinsulin (PPI) as the autoantigen. When combined with host cell-expressed TGFβ, the vaccine prevented the onset of diabetes in non-obese diabetic (NOD) mice. Herein, we investigated factors that could affect vaccine efficacy including vaccination number, optimization of the autoantigen codon sequence, Salmonella SPI2-TTSS promoter/effector combinations, concurrent short-course low-dose anti-CD3. We also evaluated autoantigen GAD65 and cytokine IL10 treatment upon vaccine efficacy. T-cells we employed to elucidate the mechanism of the vaccine action. Our results showed that GAD65+TGFβ or PPI+TGFβ+IL10 prevented the onset of diabetes in the NOD mice and maintained glucose tolerance. However, increasing the number of vaccine doses, codon-optimization of the autoantigen(s) or use of other Salmonella promoter/effector combinations had no in vivo effect. Interestingly, two doses of vaccine (PPI+TGFβ+IL10) combined with a sub-therapeutic dose of anti-CD3 prevented diabetes and decreased hyperglycemia in mice. The combined therapy also increased splenic Tregs and local Tregs in pancreatic lymph nodes (PLN) and increased regulatory (IL10 and IL2) but reduced inflammatory (IFNγ and TNFα) cytokines. Together, these results indicate that the combination of low vaccine dose number, less vaccine autoantigen expression and short-course low-dose anti-CD3 can increase regulatory mechanisms and suppress autoimmunity.